Impact of Cost of Capital, Financial Leverage, and the Growth Rate of Dividend on Market Price per Share on Nepalese Commercial Banks - Maheshwari, Poonam Memani (Kanakai Journal, 2023)
This study seeks to investigate the relationship between the Impact of cost of capital, financial leverage, and the growth rate of dividendson market price per share Nepalese commercial bank. To empirically investigate a sample of 22 commercial banks of Nepal listed in the NEPSE has been selected. The data period for the study is nine years from 2010/11 to 2018/19. The dependent variable is the market price per share whereas for independent weighted average cost of capital, debt ratio, earning per share, net profit margin, dividend per share, and growth rate of dividend are used. The data have been analyzed by using descriptive statistics, correlation, and multiple regression analysis. Empirical results indicate that all the independent variables are positively related to market price per share. The result shows that the growth rate of dividends, dividend per share earnings per share debt ratio, net profit margin, weighted average cost of capital, and market price per share are positively correlated. The regression result reveals that the beta coefficient for weighted average cost of capital is negative, but earnings per share, dividend per share, net profit margin, debt ratio, and growth have a positive beta coefficient.